Accounting for Incomplete Pass-Through - NAKAMURA, EMI; ZEROM, DAWIT (Review of Economic Studies, 2009)
Recent theoretical work has suggested a number of potentially important factors in causing incomplete pass-through of exchange rates to prices, including markup adjustment, local costs and barriers to price adjustment. We empirically analyse the determinants of incomplete pass-through in the coffee industry. The observed pass-through in this industry replicates key features of pass-through documented in aggregate data: prices respond sluggishly and incompletely to changes in costs. We use microdata on sales and prices to uncover the role of markup adjustment, local costs and barriers to price adjustment in determining incomplete pass-through using a structural oligopoly model that nests all three potential factors. The implied pricing model explains the main dynamic features of short and long-run pass-through. Local costs reduce long-run pass-through (after six quarters) by 59% relative to a Constant Elasticity of Substitution benchmark. Markup adjustment reduces pass-through by an additional 33%, where the extent of markup adjustment depends on the estimated “super-elasticity” of demand. The estimated menu costs are small (0.23% of revenue) and have a negligible effect on long-run pass-through but are quantitatively successful in explaining the delayed response of prices to costs. We find that delayed pass-through in the coffee industry occurs almost entirely at the wholesale rather than the retail level.